e-WOM Credibility on Tiktok and Youtube: Impact on Skintific Purchase Intention - Vania Konita Safera; Ratna Roostika (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This research analyzes the role of information credibility in "Electronic Word-of-Mouth (e-WOM)" on TikTok and YouTube platforms and its convincing "effect on the purchase intention of Skintific products. Involving 225 respondents obtained through Google Form, "this study used the PLS-SEM (Partial Least Square Structural Equation Modeling)" method and SPSS-based descriptive statistical analysis to test six hypotheses. The findings indicate that the credibility of information significantly influences its usefulness. The credibility of information substantially impacts its adoption. The usefulness of information notably affects purchasing. Additionally, the usefulness of information significantly influences buying intention. However, the attitude towards information does not significantly affect purchase intention, and information adoption shows that it is positive towards purchase intention. The conclusions of this study provide recommendations and suggestions for businesses to prioritize information quality, source clarity, and relevance of e-WOM content in digital marketing strategies.